The witch-cult in western Europe : a study in anthropology - Murray, Margaret Alice (Clarendon Press, 1921)
This book by Margaret Alice Murray is a wonderful resource when looking closely at the Salem Witch Trials and searching for influencing factors. Witchcraft and punitive action upon the practice of witchcraft in Europe were hugely formative for the Trials.